Preparation and properties of phosphor coating based on nanostructured yttrium-aluminum garnet and low-melting glass - O. V. Uretskaya; N. E. Drobyshevskaya; E. N. Poddenezhny; A. I. Kravchenko; T. N. Savkova (Тонкие химические технологии)
The thick-film phosphor coating on glass substrates based on nanostructured cerium doped yttrium-aluminum garnet powder and low melting glass was prepared. A new method of obtaining nanostructured powders of yttrium-aluminum garnet doped by cerium ions, based on the combustion method of nitrate salts in the presence of organic fuel is developed. The modes of synthesis, structural and spectral-luminescent characteristics of the nanostructured powders are optimized leading to garnet of chemical composition Y3-хCeхAl5O12 (х = 0.02–0.06) with the particles size of 40–60 nm, spherical form, a specific surface of 50 m2/g. The luminоus composition was prepared by mixing of components with isopropanol, further the slurry was casted on a glass substrate and dried up. The glass substrate with a covering was located in the muffle furnace, gradually heats up to temperature of 650°C and is maintained within 30-60 minutes, then slowly cooled with the furnace. Dependences of spectral-luminescent characteristics of coatings with respect to concentration of phosphor powders, nature and concentration of diffusing components of silica glass powders are revealed. At excitation on λ=440-460 nm phosphor coatings based on cerium doped yttrium-aluminum garnet with silica glass powder as filling agent demonstrate the highest luminescence intensity in the range of 500–700 nm. Model samples of discrete ceramic remote converters in the form of a thick-film covering deposed on smooth and grooved glass substrates, with concentration of the phosphor powders up to 30 mas.% are fabricated. Nanostructured phosphor coatings based on YAG:Ce powders and low-melting glass were used in construction of remote converters of light-emitting-diode lighting devices. The models of white light LED lamps were made using nanostructured phosphor coatings.